Trajectory of coastal wetland vegetation in Xiangshan Bay, China, from image time series. (November 2020) - Liu, Yongchao; Liu, Yongxue; Li, Jialin; Sun, Chao; Xu, Wenxuan; Zhao, Bingxue
Abstract: Coastal wetland vegetation is crucial for providing multiple ecosystem services. However, accurate assessment of wetland vegetation is problematic due to the challenging coastal environment. Using Xiangshan Bay (XB) in China as a typical case study, we developed a time series biological phenological approach to classifying coastal wetland vegetation using Landsat time-series images from 1984 to 2018. The results demonstrate that the total vegetation area of coastal wetlands in XB in 2018 was 85.3 km 2 . The interannual dynamics of coastal wetland vegetation area in XB in the last 35 years can be divided into three periods: increasing volatility (1984–1998), decreasing (1999–2004), and increasing volatility (2005–2018). Our results emphasize the potential of the use of the time-series biological phenological approach for monitoring coastal wetland vegetation, which can contribute to the sustainable management of coastal ecosystems. Highlights: A time-series biological phenological approach can discriminate the vegetation of coastal wetlands. Spatial distribution of coastal wetland vegetation in Xiangshan Bay in 2018 Temporal variations of coastal wetland vegetation from 1984 to 2018 A management scheme for the coastal zone based on vegetation changes is explored.